2001
DOI: 10.3390/61100881
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of (Diacetoxyiodo)arenes or Iodylarenes from Iodoarenes, with Sodium Periodate as the Oxidant

Abstract: - Easy, safe, and effective novel methods for preparing either (diacetoxyiodo)-arenes, ArI(OAc)2, or iodylarenes, ArIO2, from the corresponding iodoarenes, ArI, using sodium periodate as the oxidant are presented in this paper. In order to obtain 2- and 4-iodylbenzoic acids, the respective sodium salts of 2- and 4-iodobenzoic acids should be used as the starting substrates, because mixtures containing the corresponding iodosyl derivatives as the main products along with the intended iodyl compounds are produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 26 publications
0
92
0
5
Order By: Relevance
“…Other iodine() reagents such as PhI(OAc) 2 (PIDA) [13] have a similar effect in this coupling reaction with zincated porphyrin. Thus, mixing Zn-3aa with one equivalent of PIDA in CHCl 3 at room temperature for 2.5 h afforded the coupling product Zn-4aa quantitatively, whereas for other metalloporphyrins, such as Cu-3aa and Ni-3aa, only trace Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…Other iodine() reagents such as PhI(OAc) 2 (PIDA) [13] have a similar effect in this coupling reaction with zincated porphyrin. Thus, mixing Zn-3aa with one equivalent of PIDA in CHCl 3 at room temperature for 2.5 h afforded the coupling product Zn-4aa quantitatively, whereas for other metalloporphyrins, such as Cu-3aa and Ni-3aa, only trace Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical structures of the purified compounds in Table 1 were confirmed by satisfactory microanalyses obtained at the Institute of Organic Chemistry, the Polish Academy of Sciences, Warsaw, where also the IR spectra were recorded. We have observed that melting/decomposition points of many ArIO 2 are rather uncertain, depending not only upon the purity of crude or purified products prepared, but also upon the rate of their heating during the melting point determinations; this is why their melting points reported in the literature 1,5,6 often differ significantly. The melting points of ArIO 2 (Table 1) were uncorrected, and often accompanied by explosion.…”
Section: Methodsmentioning
confidence: 95%
“…In Part I, 1 we reported a new method for preparing iodylarenes from iodoarenes, in boiling and vigorously stirred neutral aqueous sodium periodate solutions. These reactions proceeded within 8-16 hours and gave ArIO 2 in 58-91% crude yields, having 97-99% purities established iodometrically.…”
Section: Introductionmentioning
confidence: 99%
“…So wurde beispielsweise die erfolgreiche Herstellung von IBX durch Oxidation von o-Iodbenzoesäure mit Chlor und wässrigem Natriumhypochlorit [15] oder mit wässrigem Natriumperiodat [16] berichtet. Der wohl geläufigste Zugang zu IBX wurde bereits 1936 von Greenbaum erstmals beschrieben und erfolgt durch Oxidation von o-Iodbenzoesäure mit Kaliumbromat in wässriger Schwefelsäure.…”
Section: Herstellung Von Ibxunclassified